Evaluation of different duration rice (Oryza sativa) cultivars for yield and water use efficiency under direct seeded conditions - Amit, Amit Kumar (The Indian Journal of Agricultural Sciences, 2026)
Field experiments were conducted during 2019 and 2020 to evaluate seven different duration rice cultivars (Oryza sativa L.)  (two of medium, two of mid-early and three of early or short duration), , for yield and water use efficiency under the direct seeded (aerobic) conditions relative to puddled transplanted control. Grain yield of all the short duration cultivars was at par both under the aerobic and transplanted conditions.  However, the yield of longer duration (mid-early and medium) cultivars reduced significantly under aerobic conditions compared to that under the transplanted conditions with comparatively more yield reduction in medium duration cultivars ( 26.3%) than in mid early cultivars (21.7 -22.0%). The short duration cultivars, except HKR 48, were found significantly superior to longer duration cultivars under the direct seeded conditions. The highest water use efficiency (7.74 kg/ha/mm) was achieved with HKR 49. Net income obtained from short duration cultivars under direct seeded conditions was comparable to that under transplanted conditions  but the income from medium and mid-early duration cultivars reduced significantly (by Rs. 20077/ha to Rs. 28918/ha) under direct seeding. The short duration cultivars, except HKR 48, were more profitable than the longer duration varieties under the aerobic conditions with HKR 49 fetching the highest net returns (Rs.84963/ha). It can be concluded from the results that short duration rice cultivars may be developed, identified and recommended for the success of water saving direct seeding technology of rice cultivation.